Achieving impact in research - Denicolo, Pam (Success in research, 2014)
This unique addition to the Success in Research series addresses the importance of understanding and achieving impact for the purposes of gaining research funding and reporting achieved impact for the Research Excellence Framework (REF). The book includes contributions from researchers and researcher developers who feel that impact is ill-defined and poorly understood despite its prevalence in policy documents, websites and institutional activities. This succinct and cohesive text draws on the expert contributors' collective research practice, knowledge and experience.